Are diminutive turtles miniaturized? The ontogeny of plastron shape in emydine turtles. (9th January 2013) - Angielczyk, Kenneth D.; Feldman, Chris R.
<x xml:space="preserve">Abstract</x> Miniaturization, or the evolution of a dramatically reduced body size compared to related lineages, is an extraordinarily widespread phenomenon among metazoans. Evolutionary biologists have been fascinated by miniaturization because this transition has occurred numerous times, often among close relatives, providing a model system for studying convergent evolution and its underlying mechanisms. Much of the developmental work describing the ontogeny of miniature species suggests that paedomorphosis is the predominant avenue of miniaturization. Nevertheless, specific alterations to ontogeny appear highly variable, so that even related lineages with similar miniaturized traits produce those similarities via distinct ontogenetic paths. One major vertebrate group that has been overlooked in research on miniaturization is turtles. In the present study, we examined patterns of shape change in the plastron (the ventral part of the shell) over the course of ontogeny in a small clade of turtles (Emydinae) aiming to investigate whether two independently evolved diminutive members of the clade (Glyptemys muhlenbergii and Clemmys guttata) should be considered as miniaturized. We employ geometric morphometric methods to quantify the patterns of shape change these potentially miniaturized species and their relatives undergo during ontogeny, and use molecular phylogenetic trees to reconstruct ancestral conditions and provide information on the polarity of shape changes. We find that differing changes in ontogenetic parameters relative to ancestral conditions accompany the evolution of small size in emydines: G. muhlenbergii changes the duration of ontogeny and rate of shape change, whereas C. guttata changes growth rate. The observed ontogenetic repatterning of these species is reminiscent of changes in ontogeny and life history often found in miniaturized taxa. However, we conclude that C. guttata and G. muhlenbergii are not truly miniaturized because they still produce typical adult shell morphologies, and larger emydines display comparable ontogenetic flexibility. Because no emydines carry juvenile shell features forward into adulthood, we speculate that few, if any turtles, will show paedomorphic shell traits without corresponding changes in defensive strategy because such shells may offer insufficient protection. © 2013 The Linnean Society of London